Optimasi Fasa Gerak Kromatografi Lapis Tipis dan Identifikasi Fitokimia Pada Fraksi Etil Asetat Daun dan Rimpang Houttuynia cordata (H. cordata) - Rumiki, Aida Putri Mawaddah; Julianto, Tatang Shabur; Triastuti, Asih (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
Houttuynia cordata (H. cordata) is a medicinal plant that contains various secondary metabolites, especially flavonoids that have potential biological activity. This study aims to optimize the mobile phase and evaluate the chromatographic profile of ethyl acetate fractions of H. cordata leaves and rhizomes using TLC. Separation was performed on a silica gel stationary phase with several mobile phase variations, namely n-hexane and ethyl acetate (3:7; 5:10). The results showed that the n-hexane and ethyl acetate (3:7) mobile phase provided the most optimal separation. The leaf fraction was identified to contain quercetin, quercitrin, and kaempferol, while the rhizome fraction was identified to contain quercetin and kaempferol. In conclusion, the TLC method with n-hexane and ethyl acetate (3:7) as the mobile phase is effective for separating and profiling semipolar compounds in the ethyl acetate fraction of H. cordata and has the potential to support further research. Keywords: Houttuynia cordata, Thin layer chromatography, TLC mobile phase, Phytochemical